2018
DOI: 10.1371/journal.pone.0205696
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide prevalence of mother-infant skin-to-skin contact after vaginal birth: A systematic review

Abstract: BackgroundDespite the World Health Organization’s (WHO) recommendation for immediate skin-to-skin contact (SSC) after birth, separation of mothers and infants seems to be common practice in many hospitals. It is unknown how common the practice of SSC is worldwide. Therefore, we aimed to determine the reported prevalence of SSC for healthy mothers and infants immediately after normal birth.MethodsWe systematically searched CINAHL, Medline, ProQuest Central, PubMed and the Cochrane Library for articles published… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
91
2
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(104 citation statements)
references
References 47 publications
2
91
2
9
Order By: Relevance
“…Drying the newborn within ten minutes after birth was reported by 68.8% of the respondents, while 57% of the newborn mother duo had skin to skin contact within ten minutes of birth. Skin to skin contact is an evidence-based intervention for the maintenance and regulation of body temperature of the newborn, which serves as a catalyst for breastfeeding by ensuring release of oxytocin in the rst hour (36). Another worrying nding is the onethird babies who were bathed within the rst 6 hours of birth, which is contrary to international guidance.…”
Section: Discussionmentioning
confidence: 99%
“…Drying the newborn within ten minutes after birth was reported by 68.8% of the respondents, while 57% of the newborn mother duo had skin to skin contact within ten minutes of birth. Skin to skin contact is an evidence-based intervention for the maintenance and regulation of body temperature of the newborn, which serves as a catalyst for breastfeeding by ensuring release of oxytocin in the rst hour (36). Another worrying nding is the onethird babies who were bathed within the rst 6 hours of birth, which is contrary to international guidance.…”
Section: Discussionmentioning
confidence: 99%
“…Skin to skin contact between mother and infant within 30-60 min of birth is recommended by UNICEF and WHO and has been shown to improve breastfeeding rates [119]. A review of this practice found considerable variation in the implementation of this practice with rates as low as 9.6% in the Philippines and up to 91% in Singapore [120]. Rates of early contact were much lower in infants delivered by caesarean section in Asia, but the difference was smaller in some Australian studies.…”
Section: Discussionmentioning
confidence: 99%
“…4 A pesar de sus beneficios, se conoce que el CPP se practica poco, 6 principalmente por falta de estandarización de la intervención, ausencia de guías de manejo y costos asociados a esta intervención. [7][8][9] Asimismo, faltan estudios para determinar qué momento del CPP (inmediato vs. temprano) es más efectivo y seguro. Se han reportado complicaciones asociadas al CPP como colapso súbito y apnea, con incidencias entre 2.6 y cinco casos por 100,000 nacimientos, además de muerte (hasta 1.1 muertes por 100,000 nacidos vivos).…”
Section: Introductionunclassified